Protection of Man from Natural Infection with Influenza A2 Hong Kong Virus by Amantadine: A Controlled Field Trial. Issue 5724 (19th September 1970) - Oker-Blom, N.; Hovi, T.; Leinikki, P.; Palosuo, T.; Pettersson, R.; Suni, J.
Abstract : Prophylactic administration of amantadine in doses of 100 mg. twice a day offered statistically significant protection against influenza A2 infection in a double-blind field trial involving 391 medical student volunteers during the influenza A2 Hong Kong epidemic in Helsinki in the winter of 1969. Serologically verified influenza, as measured by complement fixation and/or haemagglutination inhibition, occurred in 27 out of 192 students in the amantadine group against 57 out of 199 in the placebo group, giving a protection rate of 52%.